Assessment of Atorvastatin Effectiveness on Serum PSA Level in Hypercholesterolemic Males - Iradj Khosropanah; Siavash Falahatkar; Babak Farhat; Zhoobin Heidari Bateni; Ahmad Enshaei; Ali Akbar Allahkhah; Darya Khosropanah (Acta Medica Iranica, 2011)
The previous large retrospective studies demonstrated that treatment with Statins reduces both the incidence of prostate cancer by 50% and serum Prostate Specific Antigen (PSA) level up to 40%. However the main problem in those studies was the absence of control groups of men with hypercholesterolemia without Statin treatment. We performed a small prospective controlled clinical trial to assess the influence of the treatment with Atorvastatin on serum PSA in men with hypercholesterolemia referred to our educational and treatment center from October 2007 to March 2008. In this study, among the newly diagnosed males with hypercholesterolemia (LDL > 130 mg/dl), 40 patients with LDL more than 190 mg/dl were selected as a case group and were treated with Atorvastatin (20 mg/day). Among the same population and in the same period, another 40 patients with LDL between 130 and 190 mg/dl were selected as first control group and were treated only with low fat diet. Another 40 patients with normal serum cholesterol and without any treatment were selected as second control group. The lipid profile and serum PSA level of patients of all groups were tested at the first and third months after the therapy. After completion of data, the mean serum lipids and PSA level were measured in both visits and compared with each other by paired t-test. Also the mean PSA change in two visits between three groups was compared by ANOVA and Tukey HSD test. There was not any significant difference in mean baseline PSA between hypercholesterolemic and normocholesterolemic patients (P=0.547). In case group, mean PSA and LDL was reduced by 14.1% (P=0.0001) and 30% (P=0.0001) respectively by second visit. In first control group, mean PSA was not changed significantly (P=0.337), whereas mean LDL in this group was reduced by 9.6% (P= 0.0001). Similarly in the second control group mean PSA was not changed significantly (P=0.309) by second visit. In addition, mean change of PSA in case group was compared with first and second control groups that was significantly different (P=0.0001) whereas mean change of PSA between two control groups was not significantly different (P=0.615). The results of this study showed that: 1) Short term treatment with Atorvastatin can reduce serum PSA level, and 2) This reduction is more likely to be due to direct effect and is not related to lowering serum cholesterol levels. Thus, if results of this study are confirmed by large prospective randomized clinical trials with longer follow up period, it will be possible that Atorvastatin could be used in long term as a safe chemoprophylactic agent against prostate cancer in high risk patients.